2015
DOI: 10.1590/1678-457x.6417
|View full text |Cite
|
Sign up to set email alerts
|

Fat reduction in the formulation of frankfurter sausages using inulin and pectin

Abstract: The aim of this study was to evaluate the influence of different concentrations of inulin and pectin as fat substitutes on the chemical composition, texture, and sensory acceptance of frankfurter sausages. Six treatments were evaluated to test fat replacement: control (T0); low fat control (T1); low fat with 15% inulin (T2); low fat with 30% inulin (T3); low fat with 7.5% inulin and 7.5% pectin (T4); and low fat with 15% inulin and 15% pectin (T5). The addition of fibers increased the yield (T3 and T5; 98.96%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
65
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 38 publications
29
65
2
4
Order By: Relevance
“…The moisture content in the pâtés with inulin was signifi cantly higher (p < 0.05) compared to the control. Similar behavior was found by other authors (Cegiełka and Tambor 2012;Flaczyk et al, 2009;Keenan et al, 2014, Menegas et al, 2013Méndez--Zamora et al, 2015;Šojić et al, 2011), who reported that fi ber, including inulin, increases the water-retaining capacity and therefore the moisture content in meat products.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The moisture content in the pâtés with inulin was signifi cantly higher (p < 0.05) compared to the control. Similar behavior was found by other authors (Cegiełka and Tambor 2012;Flaczyk et al, 2009;Keenan et al, 2014, Menegas et al, 2013Méndez--Zamora et al, 2015;Šojić et al, 2011), who reported that fi ber, including inulin, increases the water-retaining capacity and therefore the moisture content in meat products.…”
Section: Resultssupporting
confidence: 88%
“…Some authors did not observe any eff ect of inulin on cooking loss in low-fat meat products (Cegiełka and Tambor, 2012). In other studies, a positive eff ect and increased yield in products containing inulin were found (Keenan et al, 2014;Ktari et al, 2014;Méndez-Zamora et al, 2015). In this study, reducing the fat content from 22.4% to 0% and replacing it with inulin gel caused a significant (p < 0.05) increase in overall cooking loss.…”
Section: Resultscontrasting
confidence: 41%
See 3 more Smart Citations